(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Judo is a Japanese martial art, philosophy and martial art without weapons, created at the end of the 19th century on the basis of jujutsu by the Japanese martial artist, who also formulated the basic rules and principles training and competition. The following article is devoted to the development of Judo in Uzbekistan